Tinjauan Kepemilikan Merek dalam Perspektif Islam - Yusniar, Yusniar (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2022)
A brand is characterized as a title, term, sign, image, or plan or a combination of them which is aiming to distinguish the products and service of one dealers to distinguish them from those of competitors.The purpose of this study is to find out the description and explanation of brand ownership in an Islamic perspective. The data collection method in this research is by using a literature study, and the data obtained are then analyzed in a qualitative descriptive manner. Based on the results of the study it can be concluded that a brand can reflect a certain level of quality, also provide legal protection for all features and aspects of the product. Futhermore, a brand can provide an intellectual asset or ownership rights, as well as provide legal protection to the brand owner. This means that a creativity or work will only be protected by the State where the work is registered. The protected works are in tangible and intangible forms such as trademarks, copyrights, patents, arts and sciences